CONSTRUCTION OF IDENTITY IN THE DIGITAL AGE AND THE MECHANISMS OF SOCIAL CONTROL - VYSOTSKA, Olha (Fìlosofìâ ta polìtologìâ v kontekstì sučasnoï kulʹturi, 2024)
The article analyzes the main approaches to understanding the nature of identity construction and the mechanisms of social control in the digital age. Digitalization, globalization, and the transition of modern society to a networked or digital state have created new conditions for constructing identity, which is becoming more flexible and changeable. A close relationship between the nature of identity formation and practices of social control has been proven. The construction of identity in the digital society is a complex process involving individuals’ interaction with technology, social media and information systems. This process serves as a form of social control, establishing norms, influencing behavior, and shaping identities by social, economic, and political interests. Social networks are becoming important channels of identity formation, where individuals interact with different groups and virtual communities. The regulatory, economic, and political control mechanisms in the digital environment are described. It is proved that online platforms contribute to the construction of social ties, which ensures social control by influencing the content and nature of interactions. They also form prevailing unified patterns and models of action, influencing the identity and social behavior of individuals. Information and communication technologies offer new opportunities for self-expression and self-identification, but at the same time pose challenges to the preservation of the personal self. Therefore, it is necessary to take these issues into account in studies of digital culture and social media. Identity is not isolated or autonomous but is formed through constant interconnections with society and under the influence of various mechanisms of social control. The subject always has the opportunity to create new forms of identity and go beyond fixed roles and functions. However, it is also important to find a balance between the use of digital technologies and the preservation of real communications, while minimizing the negative consequences.